Problematika Guru dalam Pengembangan Bahan Ajar Sejarah Lokal Banten: Studi Kasus: SMAN 2 Pandeglang - Az Zahra Laila Dhaniarti; Yuni Maryuni; Eko Ribawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the problems faced by teachers in developing local Banten history teaching materials, in class X of SMAN 2 Pandeglang. The method used in this study is qualitative, with a case study approach. This research was conducted in classes X-I, X-J, X-K and X-L. The research was conducted on August 26 - September 5, 2024. The focus of the research studied in this thesis is: the problems faced by history teachers in developing local Banten history teaching materials. The purpose of this study is: to find out the problems faced by history teachers in developing teaching materials for Banten local history. Data collection techniques used in this study were observation, interviews, questionnaires and documentation. The data analysis technique used by the researcher used the Miles and Huberman model which includes: Data reduction, Data presentation, and Verification or Conclusion drawing. The research procedure conducted is divided into three stages, namely: Pre-field stage, implementation stage and reporting stage. Based on the research results obtained by the researcher, it shows that: the problems faced by teachers in developing local Banten history teaching materials are in the emphasis of local history materials that connect with the national curriculum, resulting in limited resources to develop teaching materials, especially in the Banten region, in addition, teachers have difficulty finding references regarding local Banten historical material because cultural events or studies, especially in the Banten region, have few or even no sources of information, and some historical events and their origins are difficult to determine. Due to this problem, it affects teachers in developing local Banten history teaching materials which cannot be realized properly.